Effects from hydrogen bonding and rigidity on selectivity in tartaric acid-based chiral selectors for enantioselective liquid chromatography - Oxelbark, Joakim; Sellén, Inga-Britt (Chirality (New York, N.Y.), 2003)
Tartaric acid‐based selectors 1 ((R,R)‐O,O′‐Bis(dimethylbenzoyl)‐N,N′‐diallyl‐N,N′‐dimethyl tartaramide) and 2 ((R,R)‐N‐allyl‐O,O′‐bis(dimethylbenzoyl) tartarimide) were synthesized, immobilized on silica, and evaluated as chiral stationary phases in enantioselective chromatography. Comparison with the commercially available column Kromasil‐CHI‐1, based on selector 3 ((R,R)‐O,O′‐Bis(dimethylbenzoyl)‐N,N′‐diallyl tartaramide) resulted in the conclusion that amide NH functions are essential to chiral recognition on this sorbent. Furthermore, NH functions contribute significantly to retention of analytes except for alcohols. It was also found that flexibility of the benzoyl moieties is essential to selectivity. Chirality 15:787–793, 2003. © 2003 Wiley‐Liss, Inc.